The Influence of Product Packaging on Consumer Purchase Intention of Salwa’s Egg Snack - Maulidina; Azzahra, Nabila; Silalahi, Flora (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the influence of product packaging on consumer purchase intention of Salwa’s egg snack, a traditional product sold in Medan, Indonesia. Packaging plays a crucial role in capturing customer attention and building brand perception. This research uses a quantitative method by distributing questionnaires to 31 respondents who have purchased the snack more than once. The results show that attractive and informative packaging significantly impacts purchase intention. The t-test result (t = 8.991 > t-table 2.048) confirms a positive and significant relationship. The regression equation Y = 12.205 + 1.025X further indicates that packaging improvements lead to increased interest. Findings suggest that enhancing visual design and adding product information such as nutrition facts and expiry date can strengthen consumer trust and increase repeat purchases.